2019
DOI: 10.5897/jpbcs2018.0739
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the parental and hybrid lines- Heterosis and other genetic parameters among Capsicum annuum genotypes and their hybrids

Abstract: In most parts of the world pepper has become a popular spice that makes food hot in addition to its much needed nutrients of carotenoids and vitamins. This report has its objective to evaluate the parents and hybrid of three Nigerian pepper genotypes (Shombo, Tatase and Nsukka yellow pepper) for growth and yield; and to estimate their genetic parameters. Conventional breeding by hand pollination was adopted. The mean performance of the parents and hybrids for morpho-agronomic characters were evaluated. Heteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The fruit length and fruit weight of the hybrid combination obtained in this study was similar to the findings described by Abu et al, where the heterosis of hot pepper plants can increase fruit length and fruit weight. 43 A previous study in hot pepper proved that the heterosis could beneficially be enhanced and improved the fruit weight and fruit yield per plant. 44 The previous researcher revealed that the heterosis to the best parent of 15 intervarietal hybrids of Manzano hot pepper could yield more fruits, improve fruit quality, increase the number of seeds per fruits, seed weight, and locule number.…”
Section: Discussionmentioning
confidence: 98%
“…The fruit length and fruit weight of the hybrid combination obtained in this study was similar to the findings described by Abu et al, where the heterosis of hot pepper plants can increase fruit length and fruit weight. 43 A previous study in hot pepper proved that the heterosis could beneficially be enhanced and improved the fruit weight and fruit yield per plant. 44 The previous researcher revealed that the heterosis to the best parent of 15 intervarietal hybrids of Manzano hot pepper could yield more fruits, improve fruit quality, increase the number of seeds per fruits, seed weight, and locule number.…”
Section: Discussionmentioning
confidence: 98%
“…Os gráficos GGE Biplots destacaram as progênies P29, P50, P12, P30, P17 e P51, quando se tentou a associação com os agrupamentos originais do dendrograma, infelizmente visualiza-se na Figura 1 relativo ao dendrograma que as superiores ao obtido para produção de frutos em açaizeiros (YOKOMIZO et al, 2017;FARIAS NETO et al, 2018), podendo se considerar que os fatores ambientais não estimáveis, que atrapalham a precisão gráfica no GGE Biplots, não constituem parcela significativa das variações. Então o modelo aqui adotado tem alta confiabilidade, assemelhando-se à outras espécies amplamente domesticadas (ABU et al, 2011;DEHGHANI et al, 2012;ALIYU et al, 2014;PEPRAH et al, 2016).…”
Section: Methodsunclassified
“…Os meses se dispuseram em apenas dois mega-ambientes, divergindo de outras espécies, como em pimenteiras ( Abu et al, 2011); em produção de frutos de pêssego por três anos (CITADIN et al, 2014) O período prioritário nas avaliações é de abril até julho (período de alta pluviosidade), e de agosto a outubro (período de estiagem).…”
Section: Methodsunclassified
“…Hot pepper (Capsicum annum L.) has preventive and therapeutic properties for many ailments such as different types of cancer, rheumatism, stiff joints, bronchitis and chest colds with cough and headache, arthritis, heart arrhythmias and many other ailments [1,2]. In this regard, Pawar, Bharude [3] found chilies to hold all the best properties to be considered as a food.…”
Section: Introductionmentioning
confidence: 99%